2018
DOI: 10.1158/0008-5472.can-18-0509
|View full text |Cite
|
Sign up to set email alerts
|

Normal Breast-Derived Epithelial Cells with Luminal and Intrinsic Subtype-Enriched Gene Expression Document Interindividual Differences in Their Differentiation Cascade

Abstract: Cell-type origin is one of the factors that determine molecular features of tumors, but resources to validate this concept are scarce because of technical difficulties in propagating major cell types of adult organs. Previous attempts to generate such resources to study breast cancer have yielded predominantly basal-type cell lines. We have created a panel of immortalized cell lines from core breast biopsies of ancestry-mapped healthy women that form ductal structures similar to normal breast in 3D cultures an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 64 publications
3
60
0
Order By: Relevance
“…These observations along with our unique observations of genetic ancestry-dependent differences in ZEB1 þ cells in the normal breast, elevated number of ZEB1 þ cells in NATs compared with healthy breast tissues of women of EA ancestry, and its localization outside the ductal structures raise several questions about the function of ZEB1 þ cells in the normal and tumor adjacent normal breast. We have shown previously that cytokeratin-positive, PROCR þ /EpCAM À cells of the normal breast, which are enriched in the normal breast of AA women compared with EA women, express 50-fold higher ZEB1 compared with cytokeratinpositive, PROCR À /EpCAM þ cells of the breast (12,43). Thus, we suspect that ZEB1 þ cells in the normal breast correspond to PROCR þ /EpCAM À cells and that cancer-induced field effect leads to expansion/proliferation of such cells in the breast of EA women.…”
Section: Discussionmentioning
confidence: 93%
“…These observations along with our unique observations of genetic ancestry-dependent differences in ZEB1 þ cells in the normal breast, elevated number of ZEB1 þ cells in NATs compared with healthy breast tissues of women of EA ancestry, and its localization outside the ductal structures raise several questions about the function of ZEB1 þ cells in the normal and tumor adjacent normal breast. We have shown previously that cytokeratin-positive, PROCR þ /EpCAM À cells of the normal breast, which are enriched in the normal breast of AA women compared with EA women, express 50-fold higher ZEB1 compared with cytokeratinpositive, PROCR À /EpCAM þ cells of the breast (12,43). Thus, we suspect that ZEB1 þ cells in the normal breast correspond to PROCR þ /EpCAM À cells and that cancer-induced field effect leads to expansion/proliferation of such cells in the breast of EA women.…”
Section: Discussionmentioning
confidence: 93%
“…Floating collagen scaffold was prepared on the basis of a protocol from Linnermann and colleagues, with some modifications as detailed in Kumar and colleagues (2,11). Matrigel basement membrane (354234, Corning) was slowly thawed on ice.…”
Section: Culturing and Characterization Of Cells In 3d Collagen Or Mamentioning
confidence: 99%
“…Several protocols have been developed that support the propagation of breast epithelial cells, which, in large part, are biased toward outgrowth of basal cells (summarized in ref. 2). Several of these culture protocols utilize irradiated mouse embryonic fibroblast or human foreskin fibroblasts as feeder cells to maintain the pluripotent state of stem cells (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed a minor sub‐population of GSCs that is stable in a GSC propagating medium. Previous studies have suggested that multiple CSC subtypes may co‐exist in the same tumor . Observed increase in this minor SOX2‐low sub‐population followed BMP4‐induced state transition suggests that these cells may be further on a differentiation spectrum.…”
Section: Discussionmentioning
confidence: 86%